(3JMQjQ cJGH GhWhdhbS aj GdWdhY hGdZQhHs - (3KGHJ Hf obnqQI Hf RgQhf GdMQGfj GdUGHF, CHh GdMSf, J (B288 (3g` s; (3GhWhdhbSs
(3ChdgG (B:s
(3jbGd dHYV WdhYGJ GdchGcH hZQhHGJgG EfgG NajI hdHYVgG CfgG XGgQI CdN s
(3BNQgG (B:s
(3hPdc eG CQOfGg , BNQ GdebGdI GdKGfjI s
(3ef Qbe (B34 (3MSGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3EUdGMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs